2012
DOI: 10.2174/1874325001206010578
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Offset (3D) in Patients without Osteoarthritis – Index Values from 200 Hip Joints

Abstract: Introduction:Femoral offset (FO) is a crucial parameter for hip joint biomechanics. Reference values for FO are particularly important when joint geometry has to be reconstructed during surgical interventions. Such reference values are scarce in literature and have mainly been obtained from osteoarthritis (OA) patients. The aim of this study was to conduct a patient-specific study of FO without osteoarthritis and to create a dataset of FO index values.Materials and Methodology:One hundred (49 female, 51 male; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Esposito et al [13] also noted that 57% of their cups were within both safe zones for those who dislocated. The mean cup inclination (44°) and anteversion (15°) of dislocated hips reported in the current study reflect the standard values noted for the native hip [35]. In addition, the mean values of both inclination and anteversion were nearly identical to the recommended targets by Lewinnek et al [20].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Esposito et al [13] also noted that 57% of their cups were within both safe zones for those who dislocated. The mean cup inclination (44°) and anteversion (15°) of dislocated hips reported in the current study reflect the standard values noted for the native hip [35]. In addition, the mean values of both inclination and anteversion were nearly identical to the recommended targets by Lewinnek et al [20].…”
Section: Discussionsupporting
confidence: 85%
“…The femoral offset in the current study was 38 mm. According to Preininger et al [35], the offset of the native hip ranges from 39 to 43 mm. Therefore, the offset in our study cohort was reconstructed accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Also, thinner slices at the femoral neck region will be needed for improving the accuracy of measurements which will increase the radiation dose. In addition, another possible limitation is the difficulty to determine the true axis of the femoral shaft by scanning the proximal femur only if we want to reduce the radiation dose [32]. Measurement units: for offset, centimeters (cm); for anteversion, degrees The full-body, 3D EOS system has less radiation compared with regular and digital X-ray and CT scan [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the non-existence of side-specific differences in relation to the femoral offset. 11 Leg length showed an average shortening of 0.4 mm (SD 3.0) in the DAA group and an average lengthening of 1.28 mm (SD 4.4) in the ALMI group (p=0.001) (Table 4, Figure 1C).…”
Section: Resultsmentioning
confidence: 96%